Simulasi Rekonstruksi Citra Pada Sensor Brain ECVT (Electrical Capacitance Volume Tomography) dengan Metode ILBP (Iterative Linear Back Projection) - Nita Handayani; Kharisma Fajar H; Freddy Haryanto; Siti Nurul K; Marlin R Baidillah; Warsito P Taruno (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2017)
The purpose of this study is to simulate the sensor 32-channel Brain ECVT image reconstruction using ILBP (Iterative Linear Back Projection) methods. ECVT is a dynamic volume imaging technique that utilizes non-linear difference of electric field distribution to determine the distribution of permittivity in the sensing area. ECVT has measured the capacitance of data as a result of changes in the permittivity distribution between the electrode pairs. ECVT device consists of three main parts: helmet-shaped sensors, DAS (Data Acquisition System), PC for display and image reconstruction process. Simulation of sensor design using COMSOL Multiphysics 3.5 software, while the process of image reconstruction and analysis of the results using Matlab software 2009a. The principle of ECVT includes two stages of data collection capacitance of electrodes (forward problem) and image reconstruction from the measured capacitance (inverse problem). In the study, the simulation of image reconstruction was done by varying the object position, the number of objects and charge density of the object. From the simulation results showed that the reconstructed image with ILBP method is influenced by several parameters: the object's position in the sensor,charge density value of the object, an alpha value and the number of iterations was selected.